SYNTHESIS OF BIOFLOCCULANT TO REDUCE TURBIDITY AND REMOVE TSS FOR RAW DRINKING WATER AND TEXTILE INDUSTRY WASTEWATER - Luthfia Henviandini, Tsamara
Chemical flocculant is usually used because cost effective and high efficiency. But, this type of flocculant can cause environmental and health problems. In order to solve this problem, microbial flocculant or bioflocculant may be applied since it is more environmentally friendly. In this research, bacteria selection for bioflocculant was started by 67 bacteria. The selection was conducted through several tests with variation of treatment (bacteria + medium and supernatant), pH, and dosage which furthermore also determined their optimum condition of pH and dosage. Bacteria growth medium used was SKC broth which composed of 15 g molasses in 1 L sea water. Bacteria selected for textile wastewater is Lusi 1.1 with supernatant treatment at optimum condition of pH 8.5 and 7% dosage. Bacteria selected for raw drinking water is combination of Sutina 5 and VA 2 (1:1 ratio) with supernatant treatment at optimum condition of pH 7.5 and 5-7% dosage. Turbidity and TSS removal from both waters using selected bioflocculant showed second order kinetic reaction with turbidity removal rate constant of 0,0004 NTU-1 min-1 for textile wastewater and 0,0015 L/mg.min for raw drinking water, also TSS removal rate constant of 0,0001 NTU-1 min-1 for textile wastewater and 0,0016 L/mg.min for raw drinking water. Floc settling velocity for raw drinking water is 0,38 cm/min or 0,0063 cm/s, meanwhile for textile wastewater is 0,25 cm/min or 0,0042 cm/s.